Epidemiology, diagnosis, vaccines, and bibliometric analysis of the 100 top-cited studies on Hepatitis E virus - Tauseef Ahmad; Saima Nasir; Taha Hussein Musa; Saif Aldeen S AlRyalat; Muhammad Khan; Jin Hui (Taylor & Francis Group, 2021)
Introduction In low-income countries, Hepatitis E infection is a common cause of acute hepatitis. So far, only two recombinant vaccines (rHEV and HEV 239) have been developed against Hepatitis E virus (HEV). Of which HEV 239 is licensed in China, but is not yet available in any other country. Objective This study aims to discuss epidemiology, diagnosis, available vaccines for HEV, and provides an overview of 100 top-cited studies on HEV. Methods A bibliometric analysis was conducted on the topic "HEV" through a systematic search of the Web of Science. The keywords used were "Hepatitis E" and retrieved articles were assessed for number of attributes. Results The search returned a total of 3,235 publications, cited 95,858 times with h-index 129. The main finding for the 100 top-cited articles on HEV showed: number of authors ranging from 1 to 23, cited references range from 4 to 304, global citations score per year range from 6.61 to 175, and global citations score range from 148 to 791. Of the 100 top-cited studies, the authors who published most articles are Purcell (n = 18), Meng (n = 17), and Emerson (n = 15). Most The largest share of articles on HEV was contributed by United States of America (n = 49) with 12,795 citations. The National Institute of Allergy andInfectious Diseases was leading institute with greatest number of publications (n = 16), cited 3,950 times. Conclusions The studies conducted on HEV have increased over time. The information presented would be very useful in decision making for policy makers providing health care, and for academicians in providing a reference point for future research.